PROBLEMATIKA SUPERVISI PENDIDIKAN - Lydia Sartika; Indah Irawati; Suci Amalia (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The problem of educational supervision is a complex issue that continues to influence education systems in various countries. Educational supervision includes supervision, guidance and evaluation of teachers and the learning process in schools. This article explores various challenges that arise in the context of educational supervision, including differences in supervision approaches, lack of stakeholder involvement, inappropriate evaluation methods, and lack of training for supervisors. Apart from that, social, economic and cultural aspects also play an important role in the dynamics of educational supervision. This study highlights the need for a holistic and contextual approach in overcoming educational supervision problems in order to improve the quality of education and learning in the future. Problems in educational supervision are a major concern in efforts to improve the quality of education at various levels of education. This article explores various problematic aspects that arise during the educational supervision process, including challenges in implementing effective supervision methods, lack of support and training for supervisors, as well as obstacles in communication between supervisors and teaching staff. Apart from that, this article also discusses the impact of these problems on the development of teacher professionalism and the quality of learning in the classroom. By detailing the sources of these problems, this article provides in-depth insight into the complexities of educational supervision, as well as offering solutions that can be implemented to overcome these challenges. Collaborative efforts between related parties, intensive training for supervisors, and the implementation of a supervision approach that is responsive to the needs of teaching staff are considered important in increasing the effectiveness of educational supervision and, ultimately, improving the overall quality of education.